EVALUASI AKTIVITAS ANTIOKSIDAN JUS KULIT NANAS DENGAN RANSUM BERBEDA TERHADAP PERFORMA PUYUH (Cortunix cortunix japonica) Antioxidant Activity Evaluation of Pineapple Peel Juice Using Different Ration on Quails Performance (Cortunix cortunix japonica)Anti - Ulfa Nurrofingah; Sumiati .; Yuli Retnani (Buletin Ilmu Makanan Ternak, 2017)
This research aimed to evaluate combination of pineapple peel juice and commercial diet and self made diet on performance, and antioxidant activity of quails. This research conducted using a complete randomized design factorial (2x2). Factor A used a different water drinking between Vita Stress (J0) and pineapple peel juice (J1). Factor B used different ration between commercial diet (RK) and self made diet (RS). This research used 320 quails which kept for 5 weeks and had given 4 treatments. The results showed that pineapple peel juice application which combined with commercial diet and self made diet had no significant effect to performance and carcass percentage. Pineapple peel application had a significant effect to increase diet consumption of quails (P<0.05). The self made diet had significant effect to increase drink consumption (P<0.05). Interaction between pineapple peel juice application which combined with commercial diet or self made diet application had significant effect in reducing MDA in liver and meat of quails (P<0.05). Pineapple peel juice supplementation didn’t interfere performance and had a potential as antioxidant in quail.Keywords: carcass percentage, MDA, performance, pineapple peel juice, quails.